Ensuring robustness in scientific research, split-root assays as an example case - Lucila Salvatore; Ronald Pierik; Kaisa Kajala; Kirsten ten Tusscher (Quantitative Plant Biology)
Scientific progress relies on reproducibility, replicability, and robustness of research outcomes. After briefly discussing these terms and their significance for reliable scientific discovery, we argue for the importance of investigating robustness of outcomes to experimental protocol variations. We highlight challenges in achieving robust, replicable results in multi-step plant science experiments, using split-root assays in Arabidopsis thaliana as a case study. These experiments are important for unraveling the contributions of local, systemic and long-distance signalling in plant responses and play a central role in nutrient foraging research. The complexity of these experiments allows for extensive variation in protocols. We investigate what variations do or do not result in similar outcomes and provide concrete recommendations for enhancing the replicability and robustness of these and other complex experiments by extending the level of detail in research protocols.